Response to the ISSCR guidelines on human–animal chimera research - Koplin, Julian J. (Bioethics, 2023)
The International Society for Stem Cell Research (ISSCR) has recently released the 2021 update of its guidelines. The update includes detailed new recommendations on human–animal chimera research. This paper argues that the ISSCR recommendations fail to address the core ethical concerns raised by neurological chimeras—namely, concerns about moral status. In minimising moral status concerns, the ISSCR both breaks rank with other major reports on human–animal chimera research and rely on controversial claims about the grounds of moral status that many people will rightly reject. A more robust framework for regulating human–animal chimera research still needs to be developed.